2010
DOI: 10.1016/j.ajhg.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Centrosomal Protein CEP152 in Primary Microcephaly Families Linked to MCPH4

Abstract: Primary microcephaly is a rare condition in which brain size is substantially diminished without other syndromic abnormalities. Seven autosomal loci have been genetically mapped, and the underlying causal genes have been identified for MCPH1, MCPH3, MCPH5, MCPH6, and MCPH7 but not for MCPH2 or MCPH4. The known genes play roles in mitosis and cell division. We ascertained three families from an Eastern Canadian subpopulation, each with one microcephalic child. Homozygosity analysis in two families using genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(136 citation statements)
references
References 59 publications
2
134
0
Order By: Relevance
“…Remarkably, CPAP and CEP152 are mutated in both MCPH and Seckel syndrome, suggesting that the two disorders might represent different ends of a disease continuum [26,100,102,144]. Indeed, recent reports uncovered mutations in the Seckel genes ATR and CtIP that cause primary microcephaly without PD, whereas short stature has been noted in some individuals with mutations in the MCPH gene, CDK5RAP2 [16,89,145].…”
Section: Perspectivesmentioning
confidence: 99%
“…Remarkably, CPAP and CEP152 are mutated in both MCPH and Seckel syndrome, suggesting that the two disorders might represent different ends of a disease continuum [26,100,102,144]. Indeed, recent reports uncovered mutations in the Seckel genes ATR and CtIP that cause primary microcephaly without PD, whereas short stature has been noted in some individuals with mutations in the MCPH gene, CDK5RAP2 [16,89,145].…”
Section: Perspectivesmentioning
confidence: 99%
“…This also suggests a functional link between primary microcephaly and microcephalic dwarfism, and there is increasing evidence of overlap between these conditions (Al-Dosari et al Guernsey et al 2010;Kalay et al 2011). Several other genes encoding centrosomal proteins cause primary microcephaly (Thornton and Woods 2009;Nicholas et al 2010).…”
Section: Centrosomes and Primordial Dwarfismmentioning
confidence: 99%
“…Mutations in centrosomal proteins cause microcephaly. 17,18 Recently, it has been demonstrated that centrosomal proteins are essential for microtubule organization and centrosome motility that have important roles in axonal formation. 19 ZNF238 is a POZ/zinc finger transcriptional repressor gene.…”
Section: Deletion Of 1q43-q44 Scs Nagamani Et Almentioning
confidence: 99%